On Professional Ethics in Library and Information Science: A Critical Review - Mahdi Shaghaghi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This article aims to contribute in a critical review of the textbook “Professional Ethics in Library and Information Science”. This book was authored in 2011 by Gharamaleki, Derakhshani, and Rezaei Sharif-Abadi and published by SAMT (The Organization on Researching and Composing University Text Books in Humanities) publications. Using the conceptual analysis method, I tried to go over from extensions to conceptions and took a theoretical perspective on professional ethics. At first, I offered an analytical bibliography about references close to this work and drew its position among them, and undertook a critique about its form, format, and formal condition. Then, the main parts of the critique include an unclear shift from consequentialism language and term toward right-based term, imbalance conceptualizations, lack of concern to rights of all players of library domain, the need to take more attention toward marginal groups, the need to take policymaking approach about ethical problems, the problem of the chaotic state of the definition of librarianship in some sections, the need to study more ethical models and references.